CONVERSION OF AGRICULTURAL LAND AND ITS IMPACT ON RICE PRODUCTION IN SIGI REGENCY - Al Alamsyar; Muhammad Basir -cyio; Lien Damayanti (Tadulako University, 2018)
This research aims to assess the rate of agricultural land conversion, analyze factors affectagricultural land conversion, and analyze the impact of land conversion on rice production in Sigi District. Data analysis used is analysis of conversion rate, logistic regression analysis, and analysis of impact production. Result obtained Conversion of paddy field that happened in Sigi District from year 2009 until year 2016 which is about 20,75% or 4,499 Ha. with average value of depreciation every year equal to 2,96% or equal to 645,57 Ha.Based on the results of logistic regression analysis obtained from 7 independent variables, only 3 variables that significantly affect the land conversion that occurred. The influential variables are land area, land selling price, and number of family dependents with Prob value. <α (10%). Variables that have no effect on land conversion are length of stay, duration of farming, yield, and selling price of paddy. Based on the results of production impact analysis, obtained the lost production capacity of 39,719.81 tons of dry milled grain or about 4,467.97 tons of dry milled grain per year.